Non-communicable disease pattern in adults seeking preventive general health checkup - Shrestha, Bikash; Nepal, Bipin; Mahat, Ravi; Adhikari, Abish (Grande Medical Journal, 2019)
Non Communicable diseases (NCDs) are now endemic in low and middle income countries. Nepal had a high burden of communicable diseases (CDs) which has now been overtaken by NCDs. Although prevention and control of NCDs is prioritized in national policies and strategies, there is no proper monitoring system. This study aims to review the morbidity pattern among the adults seeking preventive general health checkup in a major tertiary care hospital in Kathmandu. 3000 cases were evaluated. 53.6% were males and 46.4% were females. The mean age of cases was 44.9 yrs. Most of the cases ranged from 40 to 60 years of age. Almost half of them were from Kathmandu district. Nearly 78% participants live a sedentary life. Abdominal obesity was seen in 27.5% of females and 21.7% of males. Nearly 49% of cases were overweight and 24% were obese. Almost 21 % of the cases were smokers and about 36% of them consumed alcohol. Only 9% are vegetarians. 10% have diabetes and 20% have hypertension. 69% of females and 43% of males have less than normal bone mineral density. The government and private sectors must focus on strengthening preventive and curative services for early detection of risk factors and management of NCDs.